توظيف التسويق الإلكتروني في إدارة العلاقة مع الزبائن ودوره في خلق الميزة التنافسية - بلخضر، مسعودة; حازم، حجلة سعيدة; عفيف، هناء (University Of Eloued جامعة الوادي, 2024)
تهدف الدراسة إلى التعرف على أهمية توظيف التسويق الالكتروني في ادارة العلاقة مع زبائن المؤسسة وانعكاس ذلك على خلق ميزة تنافسية لها، ففي عصر الرقمنة والتطور التقني في تكنولوجيا المعلومات والاتصال اتجهت العديد من المؤسسات إلى الاستثمار في إدارة العلاقة مع زبائنها والبحث عن السبل الكفيلة بتقديم أسرع الخدمات وأحسنها واتخاذ أفضل السياسات التسويقية الملائمة لرغباتهم وتطلعاتهم، ومن بين هذه الأساليب هو استخدام التسويق الالكتروني الذي يسمح لها بإدارة علاقاتها مع زبائنها وضمان التواصل المستمر معهم ومتابعة احتياجاتهم والتفاعل مع طموحاتهم الشرائية، ما يؤدي إلى الرفع من ولائهم وتحقيق الربح، وبالتالي زيادة قدراتها التنافسية. Abstract: The study aims to identify the importance of using e-marketing in customer relationship management and its reflection on creating a competitive advantage for the organization. In the era of digitization and technical development in information and communication technology, many institutions have turned to investing in managing the relationship with their customers and searching for ways to provide the fastest and best services and adopt the best marketing policies that suit their desires and aspirations. Among these methods is the use of e-marketing, which allows them to manage their relationships with their customers and ensure continuous communication with them, follow up on their needs and interact with their purchasing ambitions, which leads to increasing their loyalty and achieving profit, and thus increasing their competitive capabilities.
مداخلة
Keywords: التسويق الالكتروني; إدارة العلاقة مع الزبائن; الميزة التنافسية